2013
DOI: 10.1371/journal.pone.0066135
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of HIV-2 and HIV-1/HIV-2 Dually Seropositive Adults in West Africa Presenting for Care and Antiretroviral Therapy: The IeDEA-West Africa HIV-2 Cohort Study

Abstract: BackgroundHIV-2 is endemic in West Africa. There is a lack of evidence-based guidelines on the diagnosis, management and antiretroviral therapy (ART) for HIV-2 or HIV-1/HIV-2 dual infections. Because of these issues, we designed a West African collaborative cohort for HIV-2 infection within the framework of the International epidemiological Databases to Evaluate AIDS (IeDEA).MethodsWe collected data on all HIV-2 and HIV-1/HIV-2 dually seropositive patients (both ARV-naive and starting ART) and followed-up in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 46 publications
1
29
0
Order By: Relevance
“…Unfortunately we had no information on the clinical stage of the patients at ART initiation. In the same study, the median CD4 count at the ART initiation was 166 cells/mm 3 , IQR (83-247) among HIV-2 infected patients and 146 cells/mm 3 , IQR (55-249) among dually seropositive [19]. Certainly because of long-term triple therapy, median CD4…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Unfortunately we had no information on the clinical stage of the patients at ART initiation. In the same study, the median CD4 count at the ART initiation was 166 cells/mm 3 , IQR (83-247) among HIV-2 infected patients and 146 cells/mm 3 , IQR (55-249) among dually seropositive [19]. Certainly because of long-term triple therapy, median CD4…”
Section: Discussionmentioning
confidence: 88%
“…Thus, a previous study reported in 2013, in both ARV-naive and starting ART and followed-up in clinical centres in West Africa, that overall, 16.7% of HIV-2 patients on ART had an advanced clinical stage (WHO IV or CDC-C) [19]. Unfortunately we had no information on the clinical stage of the patients at ART initiation.…”
Section: Discussionmentioning
confidence: 88%
“…In such settings, commercial nonnucleic acid-based methods, such as the Cavidi ExaVir Load assay, can be a good alternative considering the low cost, simple and standardized procedure, and limited physical requirements (60). Moreover, in African countries such as Cape Verde (13,14,61), Guinea-Bissau (62), Gambia (63), and Senegal (64,65), where HIV-1 and HIV-2 cocirculate, but also in Portugal (38)(39)(40) and France (66,67), the characteristics of the ExaVir Load assay make it useful to measure viral load in patients infected with HIV-1 and/or HIV-2, provided that the serologic diagnosis of HIV-1 or HIV-2 infection is well established in advance.…”
Section: Discussionmentioning
confidence: 99%
“…In these regions, the cocirculation of HIV-1/M and HIV-2 or HIV-1/O leads to dual infections (12)(13)(14)(15)(16)(17)(18)(19)(20)(21). In West Africa, dual infections with HIV-1 and HIV-2 (referred to as HIV-1ϩHIV-2) are thought to account for 1 to 8% of HIV infections (17,22), although no HIV-1/2 recombinant has yet been described. In West-Central Africa, including Cameroon in particular, the frequency of HIV-1/MϩO dual infections has been estimated to be 10% in the HIV-1/O-seropositive population (20,23,24).…”
mentioning
confidence: 99%
“…They also have an impact on clinical practice, because they may interfere with the results obtained with serological and molecular tools for diagnosis and patient follow-up. Some serological tools are less sensitive to HIV-1/O (30) or HIV-2 (22,31) and may behave similarly with recombinants carrying a group O-derived envelope or with cryptic HIV-1ϩHIV-2 infections (17). Similarly, variants may affect the determination of viral load (VL) by quantitative RT-PCR (32)(33)(34)(35).…”
mentioning
confidence: 99%